PENGARUH TINGKAT INFLASI, SUKU BUNGA, HARGA EMAS DUNIA, DAN KURS RUPIAH PADA JII - Utoyo, Novita Ndari; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is meant to analyze the influence of inflation rates, interest rates of Certificate of Bank Indonesia, the price of gold, and Rupiah current exchange rate to the Syariah stock index which is Jakarta Islamic Index (JII). This research is a comparative causal research. The sample collection technique has been done by using purposive sampling. The samples are 60 JII Indexes from 2010 to 2014. The data is the secondary data which has been done by using documentation method in the form of statistics data and index summary of 2010-2014 periods which has been obtained from Indonesia Stock Exchange (IDX) and Bank Indonesia (BI). The data analysis method has been done by using multiple linear regressions analysis. The result of the research shows that : (a) the inflation rates does not have any influence to the Jakarta Islamic Index (JII) because the inflation that has occurred is the lowest; (b) the interest rates of Certificate of Bank Indonesia does not have any influence to the Jakarta Islamic Index (JII) because for the investors, the interest rates of Certificate of Bank Indonesia is riba; (c) the price of gold has positive influence to the Jakarta Islamic Index (JII) because the due to the enhancement of gold price has led investors to sell their gold, and gain benefit, then they allocate their investment to Syariah stocks; (d) Rupiah current exchange has negative influence to the Jakarta Islamic Index (JII) because for the investors when the currency is weakening, it means that the prospect of the economy is unfavorable and high risk if the stocks are not sold.Keywords: Inflation rates, interest rates, the price of gold, rupiah current exchange, and Index (JII).